2013
DOI: 10.1128/jvi.02063-12
|View full text |Cite
|
Sign up to set email alerts
|

SUMOylation Affects the Interferon Blocking Activity of the Influenza A Nonstructural Protein NS1 without Affecting Its Stability or Cellular Localization

Abstract: Our pioneering studies on the interplay between the small ubiquitin-like modifier (SUMO) and influenza A virus identified the nonstructural protein NS1 as the first known SUMO target of influenza virus and one of the most abundantly SUMOylated influenza virus proteins. Here, we further characterize the role of SUMOylation for the A/Puerto Rico/8/1934 (PR8) NS1 protein, demonstrating that NS1 is SUMOylated not only by SUMO1 but also by SUMO2/3 and mapping the main SUMOylation sites in NS1 to residues K219 and K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 82 publications
(100 reference statements)
1
40
0
Order By: Relevance
“…We and others have demonstrated that several viral proteins are sumoylated in transfected and infected cells; we previously demonstrated that NS1 is sumoylated at C-terminal residues in infected cells and that sumoylation stabilizes NS1 for efficient viral replication (8). Another group confirmed our finding that the C-terminal lysine is the major sumoylation site and that sumoylation ensures NS1 function (29). Sumoylation of M1 has also been reported and found to be involved in virus assembly (9).…”
Section: Discussionsupporting
confidence: 86%
“…We and others have demonstrated that several viral proteins are sumoylated in transfected and infected cells; we previously demonstrated that NS1 is sumoylated at C-terminal residues in infected cells and that sumoylation stabilizes NS1 for efficient viral replication (8). Another group confirmed our finding that the C-terminal lysine is the major sumoylation site and that sumoylation ensures NS1 function (29). Sumoylation of M1 has also been reported and found to be involved in virus assembly (9).…”
Section: Discussionsupporting
confidence: 86%
“…The nonstructural NS1 protein is the first discovered and the most frequent SUMO target of IAV, which is SUMOylated to facilitate viral replication73. Our results showed that the SUMOylation of the small GTP-binding protein Rac1 was competitively inhibited by the viral NS1 protein in the host cell, indicating that IAV profoundly relied on SUMOylation to survive in host cells.…”
Section: Discussionmentioning
confidence: 70%
“…However, PR8 NS1 has been found to inhibit the IFN response by human dendritic cells by a lesser degree than human isolates of IAV (Haye et al, 2009). Furthermore, the multiple functions of NS1 are regulated by post-translational modification, including phosphorylation, SUMOylation, and ISGylation (Hsiang et al, 2012; Santos et al, 2013; Zhao et al, 2010). It is unknown how these modifications of NS1 might affect IFN antagonism by PR8 specifically in ATII cells.…”
Section: Resultsmentioning
confidence: 99%